1993
DOI: 10.1016/0016-7061(93)90064-r
|View full text |Cite
|
Sign up to set email alerts
|

Comparative study of soil organic layers in two bilberry-spruce forest stands (Vaccinio-Piceetea). Relation to forest dynamics

Abstract: Morphologica1 features of twelve humus profiles demonstrating the diversity of vegetation types present in subalpine forests were compared, together with soil fauna. Two forest stands of spruce [Picea abies (L.) Karst.] in association with bilberry (Vaccinium myrtillus L.), located at 1630 and 1880 m altitude (Mâcot-La Plagne, Tarentaise valley, Savoy, France), were studied. Morphological observations of small soil volumes were made on disturbed samples by the method of Ponge, but here transformed into quantit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

1994
1994
2015
2015

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(16 citation statements)
references
References 18 publications
1
15
0
Order By: Relevance
“…Similar results of his and our study are: (1) similar species richness regardless of successional stage; (2) decrease of earthworm biomass in the subclimax plant community; (3) increase in the proportion of epigeic species; (4) stable abundance in a short (5 year) period in the forest earthworm community; and (5) species associated only with oldest forests. Earthworm abundance was also lower in later stages of succession of an alpine spruce forest in France [1].…”
Section: Discussionmentioning
confidence: 92%
“…Similar results of his and our study are: (1) similar species richness regardless of successional stage; (2) decrease of earthworm biomass in the subclimax plant community; (3) increase in the proportion of epigeic species; (4) stable abundance in a short (5 year) period in the forest earthworm community; and (5) species associated only with oldest forests. Earthworm abundance was also lower in later stages of succession of an alpine spruce forest in France [1].…”
Section: Discussionmentioning
confidence: 92%
“…The patches of forests in various stages of succession are adjacent at SERC and there are no physical barriers between stands of different ages keeping earthworms from migrating, which suggest a natural decline in earthworm abundance occurs with stand maturation (Szlavecz and Csuzdi 2007). Further, other studies in France and the Czech Republic showed that earthworm abundance declines along a successional gradient (Pižl 1992;Bernier et al 1993). Historic land-use, propagule pressure, or small differences in pH may reduce populations in later successional forests.…”
Section: Tree Species As a Driver Of Pom Chemistrymentioning
confidence: 94%
“…Annelids create different structures according to their size, macro-(> 4 mm) and meso-structures (2-4 mm) of mull and amphi humus forms resulting from the burrowing and defecating activity of earthworms (Galvan et al, 2008), while microstructures (< 2 mm) of moder humus forms result mainly from the activity of enchytraeids (Didden, 1990;Dawod and FitzPatrick, 1993;Ponge, 1999). Enchytraeids, in particular the common, asexual Cognettia sphagnetorum, replace earthworms when conditions become more severe along latitudinal and altitudinal gradients (Bernier et al, 1993;Briones et al, 2007). Exclusion mechanisms between enchytraeids and earthworms, whether competitive or behavioral in advance of competition, have been demonstrated (Haukka, 1987;Ponge, 2003), in addition to abovementioned differences in tolerance, which might explain observed gradients of annelid composition and resulting changes in humus forms (Ponge, 2003).…”
Section: Discussionmentioning
confidence: 99%